Experiential learning: visiting libraries in southern California - Caudillo Ruiz, Dora Yessica (My University, 2019)
Abstract: This research work consists off a qualitative analysis starting from a field practice that was born from the necessity to access information and knowledge as part of the Information Management curriculum subject. The study was conducted in CETYS University, located in Tijuana, Baja California, Mexico. It is a private institution that caters High School and High Education; this case presents the results on a sample taken from a population of more than a thousand students that have visited several libraries from Southern California in the past four years. In 2015, the institution implemented a program that promoted information culture within the students teachers and administrative personnel. Such program included diverse actions like installing technological equipment in the classrooms, update infrastructure, digital databases and expanding printed and multimedia library collections, as well as training current library staff and hiring specialized personnel, among other actions; the course Information Management was designed to promote informational skills in students; so the curricular content of this subject focuses on developing skills to access, evaluate and use information. To fulfill the purposes of the program, the teachers designed an exercise that consisted of a series of visits to different libraries, in order for the students to access other collections and expand their information sources. However, it was observed that the exercise involved other experiential factors that had a positive impact on the student's education; not only did they accessed other information sources, but their experience transcended the goal of the class activity. Geographic location is a determining factor for this case study; the proximity of the Tijuana and San Diego cities, has generated a binational link that has historically characterized this region of the Mexican border with the United States. The relationship between the both cities has been strengthened by librarian cooperation ties; the proximity has facilitated the transit and access between regions, successfully achieving the goal of this exercise which involves students visiting following libraries: San Diego State University (SDSU), University of California at San Diego (UCSD) and The Public Library of San Diego. The method used for data collection was through active observation; the teacher was in charge of taking evidence of the attitude and behavior of the students through images and video. Subsequently, a focus group was created with students from different careers in which they were interviewed and asked to describe their experience. The results indicate that experiential learning is an alternative that encourages meaningful learning; "The student relates the new information with the information he already knows, readjusting and reconstructing both information of the process" (Ausubel, 1983). This type of knowledge remains in the students, because they have confirmed its veracity by themselves; in addition, it strengthens teamwork and the current and efficient way to use the available information resources. This activity is considered as a globalizing strategy and promotes working cooperatively, factors that are in tune with the educational principles of CETYS University
Keywords: Active learning; Binational librarian cooperation; Information culture; Information management; Library-academia linkage; Campus Tijuana